VARIABEL ANTASEDEN DAN KONSEKUENSI DARI KINERJA KUALITAS : STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR DENGAN STANDAR NASIONAL INDONESIA - Handayani, Dwi (Jurnal Analisis Bisnis Ekonomi, 2009)
The purpose of this study are to investigate the influence of quality management control systems (quality goal, quality feedback, quality incentives) and environmental accounting on quality performance, the influence of quality performance on both financial performance and customer satisfaction, and the impact of customer satisfaction on financial performance. Data used for this study was collected from financial, production and marketing manager to manufactur company with SNI. Data collected by mail survey 1250 questinnaries. The questionnaries that useful for analysis were 149. Analysis conducted by SEM with AMOS ver 5.0. The result indicates that communication intensity of quality goal toward the labour is not related to quality performance. The frequency of quality feedback is not related to quality performance. The improvement of incentive which is in relation with quality has a positive relationship with quality performance. The implementation of Quality performance has a positive relationship with the customer satisfaction. Quality performance has a positive relationship with financial performance. Customer satisfaction is not related to financial performance.